2004
DOI: 10.1038/sj.gene.6364161
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 18 promoter polymorphisms are not strongly associated with type I diabetes in a UK population

Abstract: Interleukin 18 (IL18) is a proinflammatory cytokine whose levels are increased in the subclinical stage of insulin-dependent (type I) diabetes mellitus. Previous case-control studies have reported associations between IL18 À607C4A and À137G4C promoter polymorphisms and type I diabetes. We performed case-control and family-based association studies employing Pyrosequencing to assess if these IL18 polymorphisms are also associated with the development of type I diabetes in the Northern Ireland population. The w … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…The observed genotype frequencies were in accordance with Hardy-Weinberg equilibrium. The allele distribution and haplotypes of the control group were previously published [26] and were similar to other reports on Caucasian populations [27]. We found no association of IL-18 -137 or -607 polymorphism with age (p ϭ 0.085 and p ϭ 0.873, respectively) or gender (p ϭ 0.310 and p ϭ 0.530, respectively).…”
Section: Il-18 Genotypes and Cancer Risksupporting
confidence: 88%
“…The observed genotype frequencies were in accordance with Hardy-Weinberg equilibrium. The allele distribution and haplotypes of the control group were previously published [26] and were similar to other reports on Caucasian populations [27]. We found no association of IL-18 -137 or -607 polymorphism with age (p ϭ 0.085 and p ϭ 0.873, respectively) or gender (p ϭ 0.310 and p ϭ 0.530, respectively).…”
Section: Il-18 Genotypes and Cancer Risksupporting
confidence: 88%
“…Ide et al (22) found that a higher promoter activity of haplotype -137G/-607C of the IL-18 gene might increase the expression of IL-18, resulting in upregulation of the IFN-γ-producing T-cells. It is reported that the two loci (-137 C/G, -607 A/C) were in LD (19,24). Lastly, clinical heterogeneity might also explain the discrepancy.…”
Section: Discussionmentioning
confidence: 85%
“…The potential contribution of differences in patient populations (e.g., age and years from onset, as well as disease severity) might lead to different results. In the study by Martin et al (24), the age at diagnosis of cases was under 15 years, whereas in the Polish and Japanese studies the age at diagnosis was under 30 years.…”
Section: Discussionmentioning
confidence: 96%
“…The IL-18 C-607A SNP is a common polymorphism with allele frequencies that are dependent on ethnic background. For example, in Han Chinese, the frequency of the A allele is 51.3-53.0% (Dong et al 2007;Yu et al 2009;Zhang et al 2005), whereas in British Caucasians the A allele is less frequent, 35.7-40.8% (Gracie et al 2005;Martin et al 2005). In this study, distributions of the IL-18 C-607A SNP were determined and compared in healthy Singaporean Chinese, Indians, and Malays.…”
Section: Introductionmentioning
confidence: 98%